Enhanced recovery protocols in patients undergoing pancreatic surgery: An umbrella review - Jing Li; Frances Lin; Shuhui Yu; Andrea P. Marshall (Wiley, 2022)
Abstract Aim To identify, synthesize and appraise the systematic reviews of ERAS for patients undergoing pancreatic surgery and facilitate ERAS implementation. Design An umbrella review was used to identify systematic reviews. Methods A systematic search following the PRISMA guidelines was used to search databases including PubMed, Embase, Cochrane Library, CINAHL, CNKI, WanFang and VJIP. AMSTAR 2 was used to appraise the quality of included reviews. Results Ten systematic reviews were included. The quality of all included systematic reviews was rated as "critically low." The most frequently reported ERAS elements were epidurals analgesia/PCA (9/10), goal‐directed mobilization (9/10) and early removal of drains (9/10). Only one review mentioned audit protocol compliance. None of the included reviews reported discharge standards. Ten reviews reported decreased length of stay, seven reviews reported lower hospital costs, and six reviews reported decreased total complications rate. There were no adverse effects reported.